Six screening instruments for frailty in older patients qualified for emergency abdominal surgery. Issue 3 (November 2015) - Kenig, Jakub; Zychiewicz, Beata; Olszewska, Urszula; Barczynski, Marcin; Nowak, Wojciech
Highlights Six frailty screening tests in elderly patients undergoing emergency surgery. The VES-13: the best screening instrument; highest sensitivity and negative predictive value. Allows for tailored treatment of high-risk group of elderly patients.